Hand proximity facilitates spatial discrimination of auditory tones - Tseng, Philip; Yu, Jiaxin; Tzeng, Ovid J. L.; Hung, Daisy L.; Juan, Chi-Hung (Frontiers in Psychology, 2014)
The effect of hand proximity on vision and visual attention has been well documented. In this study we tested whether such effect(s) would also be present in the auditory modality. With hands placed either near or away from the audio sources, participants performed an auditory-spatial discrimination (Exp 1: left or right side), pitch discrimination (Exp 2: high, med, or low tone), and spatial-plus-pitch (Exp 3: left or right; high, med, or low) discrimination task. In Exp 1, when hands were away from the audio source, participants consistently responded faster with their right hand regardless of stimulus location. This right hand advantage, however, disappeared in the hands-near condition because of a significant improvement in left hand’s reaction time. No effect of hand proximity was found in Exp 2 or 3, where a choice reaction time task requiring pitch discrimination was used. Together, these results suggest that the effect of hand proximity is not exclusive to vision alone, but is also present in audition, though in a much weaker form. Most important, these findings provide evidence from auditory attention that supports the multimodal account originally raised by Reed et al. in 2006.